Predictivity of early and late assessment for post-surgical recurrence of Crohn's disease: Data from a single-center retrospective series. Issue 8 (August 2021) - Dal Piaz, Giulia; Mendolaro, Marco; Mineccia, Michela; Randazzo, Claudia; Massucco, Paolo; Cosimato, Maurizio; Rigazio, Caterina; Guiotto, Cristina; Morello, Enrico; Ercole, Elena; Lavagna, Alessandro; Rocca, Rodolfo; et al.
Abstract: Background and Aims: Post-surgical recurrence of Crohn's disease (CD) after ileocolonic resection is common. Early identification of features associated with recurrence is a standard procedure of postoperative management, but the prognostic role of such features when detected at later time points is unclear. We compared the predictivity for Crohn's disease recurrence of common clinical–instrumental variables when assessed early (<12 months) or late (>36 months) after surgery. Methods: This retrospective study considered CD patients who had ileocolonic resection and were followed for a median of 7.6 years. Clinical characteristics, post-surgical therapy, endoscopy recurrence (Rutgeerts' score ≥i2) and ultrasound features were compared between subgroups who had a early or late post-surgical assessment. Univariate and multivariate analyses were done to identify variables associated with recurrence (clinical and surgical). Results: Of 201 patients, 70 (32%) had a early and 39 (19%) had a late post-surgical assessment. The Early and Late subgroups had similar clinical characteristics. Overall, clinical relapse was observed in 131 patients (66%), surgical relapse in 31 (16%), endoscopic recurrence in 149 (75%) and ultrasonographic recurrence in 132 (66%), without significant differences in frequencies between subgroups. By Cox proportional hazard regression, endoscopic recurrence was a significant predictor of clinical recurrence overall (HR=2.31, P = 0.002) and in the Early (HR=3.85, P = 0.002) but not Late subgroup. Discussion: The most informative postoperative CD assessment is the one done within the first year of surgery. Later endoscopic evaluations have no prognostic value and should be done only for clinical needs or for research purposes.